Comparative Genomics of Novel Agrobacterium G3 Strains Isolated From the International Space Station and Description of Agrobacterium tomkonis sp. nov. - Singh, Nitin K.; Lavire, Céline; Nesme, Joseph; Vial, Ludovic; Nesme, Xavier; Mason, Christopher E.; Lassalle, Florent; Venkateswaran, Kasthuri (Frontiers in Microbiology, 2021)
Strains of Agrobacterium genomospecies 3 have been previously isolated from diverse environments, including in association with plant roots, with algae, as part of a lignocellulose degrading community, from a hospital environment, as a human opportunistic pathogen, or as reported in this study, from a surface within the International Space Station. Polyphasic taxonomic methods revealed their relationship to Agrobacterium G3, which further support the description of a novel species. The G3 strains tested (n=9) were phenotypically distinguishable among the strains from other genomospecies of the genus Agrobacterium. Phylogenetic analyses of the 16S rRNA gene, gyrB gene, multi-locus sequence analysis, and 1,089-gene core-genome gene concatenate concur that tested G3 strains belong to the Agrobacterium genus and they form a clade distinct from other validly described Agrobacterium species. The distinctiveness of this clade was confirmed by average nucleotide identity (ANI) and in silico digital DNA–DNA hybridization (dDDH) comparisons between the G3 tested strains and all known Agrobacterium species type strains, since obtained values were considerably below the 95% (ANI) and 70% (dDDH) thresholds used for the species delineation. According to the core-genome phylogeny and ANI comparisons, the closest relatives of G3 strains were Agrobacterium sp. strains UGM030330-04 and K599, members of a novel genomospecies we propose to call genomovar G21. Using this polyphasic approach, we characterized the phenotypic and genotypic synapomorphies of Agrobacterium G3, showing it is a bona fide bacterial species, well separated from previously named Agrobacterium species or other recognised genomic species. We thus propose the name Agrobacterium tomkonis for this species previously referred to as Agrobacterium genomospecies 3. The type strain of A. tomkonis is IIF1SW-B1T (=LMG 32164 = NRRL B-65602). Comparative genomic analysis show A. tomkonis strains have species-specific genes associated with secretion of secondary metabolites, including an exopolysaccharide and putative adhesins and resistance to copper. A. tomkonis specific gene functions notably relate to surface adhesion and could be involved to colonize nutrient-poor and harsh habitats. The A. tomkonis strains showed presence of a 40-kbp plasmid and several other potential mobile genetic elements detected that could also be part of conjugative elements or integrated prophages.